PEMETAAN PUBLIKASI ILMIAH TENTANG PERPUSTAKAAN DIGITAL TAHUN 2011-2021 MELALUI APLIKASI VOSViewer (MAPPING SCIENTIFIC PUBLICATIONS ABOUT DIGITAL LIBRARY 2011-2021 THROUGH VOSViewer APPLICATION) - Salsabiila Anjani; Yunus Winoto (JURNAL ILMU PERPUSTAKAAN (JIPER), 2022)
Abstract.  A digital library is a library that already has a collection in digital form, and can serve its users boldly without having to come directly to the library building. The digital library is a technological innovation to make it easier for users to meet their needs. This study aims to determine the trend of scientific publications about digital libraries in Indonesia based on keywords that often appear, the authors who discuss this topic, and how many scientific publications have been published with the keywords digital library in the 2011-2021 timeframe. The method used is a quantitative descriptive method with a bibliometric approach. Scientific publication data is taken from the Google Scholar database using the Harzing's Publish or Perish application by entering the keyword “digital library” then the data is processed in the VOSviewer application. The results of this study found that the co-occurrence that appears is more words related to technology. In addition, the results are also divided into 7 clusters of keywords that appear most often in each cluster. For the most prolific authors, there are 18 top authors with at least 4 scientific publications and the most prolific writer is Rodin, R. with 11 scientific publications. The conclusion of this study is that the trend of scientific publications regarding digital libraries has experienced positive growth along with the development of technology with the appearance of the VOSviewer visualization.Keyword: knowledge mapping, bibliometrics, VOSviewer, digital library.